Association between Oral Health-Related and Health-Related Quality of Life - Sekulić Stella; John Mike T.; Davey Cynthia; Rener-Sitar Ksenija (Sciendo, 2020)
To investigate the correlation between the four dimensions of Oral Health-Related Quality of Life (OHRQoL) and Health-Related Quality of Life (HRQoL) constructs in a dental patient population.